1963
DOI: 10.1139/m63-067
|View full text |Cite
|
Sign up to set email alerts
|

Release of Ultraviolet-Absorbing Material From Escherichia Coli at Subzero Temperatures

Abstract: When cells of Escherichia coli were suspended in dilute artificial seawater and cooled to various subzero temperatures, a maximum lethal effect occurred around −40 °C. In addition, rapid cooling to −26 °C of bacteria, suspended in concentrated, non-freezing seawater caused a pronounced decrease in viability ("cold shock"). The loss in viability was accompanied by a proportional release from the cells of ultraviolet-absorbing material and by an increase in the ribose and organic phosphorus contents of the suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It is clearly demonstrated in the present study that inhibilioii of endogenous respiration was paralleled bj' leaking of VY absorbing substances from the cells. The absorbance characteristics of these substances (Figtu'e 6) are very similar to those obtained for instance for materials released from Escherichia coli upon freezing and thawing (Lindeberg and Lode 1963), and from Merulius Utcrymans when grown at supraoplimal temperatures (Langvad and Goksoyr 1967). Consequently, vai'ious organisms seem to respond to quite different treatments with the same type of leaking.…”
Section: Discussionsupporting
confidence: 71%
“…It is clearly demonstrated in the present study that inhibilioii of endogenous respiration was paralleled bj' leaking of VY absorbing substances from the cells. The absorbance characteristics of these substances (Figtu'e 6) are very similar to those obtained for instance for materials released from Escherichia coli upon freezing and thawing (Lindeberg and Lode 1963), and from Merulius Utcrymans when grown at supraoplimal temperatures (Langvad and Goksoyr 1967). Consequently, vai'ious organisms seem to respond to quite different treatments with the same type of leaking.…”
Section: Discussionsupporting
confidence: 71%
“…Absence of death and injury among cells frozen and stored at -198°C and the obvious death and injury among cells that were frozen at -198°C and stored at -18°C suggested that lethal and sublethal effects occurred primarily during frozen storage. This may have been caused by growth of ice crystals and concentration of solutes rather than cold shock which has been suggested as the chief factor in killing bacterial cells during freezing (Hilliard and Davis, 1918;Lindeberg and Lode, 1963). Moss and Speck (1963) Seven freeze-thaw cycles of L. monocytogenes in PB stored at -198°C resulted in 18.7% death and 0% injury (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Damage to membranes has been shown to lead to the leakage of internal cell materials such as potassium ions, P-galactosidase and low molecular UV-absorbing materials (Lindeberg & Lode, 1963;Calcott & MacLeod, 1975). The release of these substances has been correlated negatively with cell viability.…”
Section: Studies Of Microbial Growth and Survival In Frozen Food Systemsmentioning
confidence: 99%